Novel VANET using a simultaneous wireless updown link - Somsak Mitatha; Montree Bunruangses; Khamron Sunat; P. P. Yupapin (My University, 2010)
Abstract We propose a new design of a Vehicular Ad Hoc network (VANET) system that uses the dense wavelength division multiplexing wavelength enhancement, whereas the increasing in channel capacity and signal security can be provided. The increasing in number of channel can be obtained by the increasing in wavelength density, while the security is introduced by the specific wavelength filter, which is operated by the central operator. The optical communication wavelength enhancement is reviewed. The advantage is that the proposed system can be implemented and used incorporating with the existed communication link in either wire/wireless system, where the privacy can be provided, which is discussed in detail. © 2010 Wiley Periodicals, Inc. Microwave Opt Technol Lett 52: 1764–1768, 2010; Published online in Wiley InterScience (www.interscience.wiley.com). DOI 10.1002/mop.25328
Keywords: Vehicular Ad Hoc Networks (VANETs)